Two new species of Nomuraius Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from southern China - Huang, Meng-Chi; Yin, Zi-Wei (Zootaxa, 2018)
Two new Chinese species of the tyrine genus Nomuraius Hlaváč, N. excavatus Huang & Yin, sp. n. (Guangxi), and N. nanlingensis Huang & Yin, sp. n. (Guangdong), are described and illustrated. The identification key and distributional map of the genus are updated to include the new data.